Pear Wood Pyrolysis Influences Quality and Levels of Polycyclic Aromatic Hydrocarbons in Liquid Smoke - Mingwu Qiao; Fei Wang; Shaohua Meng; Yufei Liu; Lianjun Song; Jiansheng Zhao; Yan Ma; Guanghui Zhao; Xianqing Huang; Dan Hai (Journal of Food Protection, 2024)
Limu smoked chicken is a traditional Chinese delicacy; however, polycyclic aromatic hydrocarbons (PAHs) are generated during the smoking process. We developed a pyrolysis process for pear wood liquid smoke with minimal PAH generation. Pear wood liquid smoke products were prepared under different pyrolysis conditions in a self-made pyrolysis reactor, and the total phenol, carbonyl compound, total acid, and PAH contents and PAH toxicity risk were evaluated. With increasing temperatures, the toxicity equivalent ΣPAH of the smoke liquid reached 3.004 μg/kg. With increasing particle sizes, the total phenol content reached 1.6 mg/mL; the phenol content was 5.95 mg/mL. With increasing particle sizes, the toxicity equivalent ΣPAHs of the smoke liquor reached 2.441 μg/kg. The optimal parameters for treating pear wood smoke liquid in the thermal reaction device were a pyrolysis temperature of pear wood of >350 °C, particle size of S2, and sucrose content of 8%.